2018
DOI: 10.15252/embj.201899819
|View full text |Cite
|
Sign up to set email alerts
|

EGR 2 phosphatase regulates OST 1 kinase activity and freezing tolerance in Arabidopsis

Abstract: OST1 (open stomata 1) protein kinase plays a central role in regulating freezing tolerance in Arabidopsis; however, the mechanism underlying cold activation of OST1 remains unknown. Here, we report that a plasma membrane-localized clade-E growth-regulating 2 (EGR2) phosphatase interacts with OST1 and inhibits OST1 activity under normal conditions. EGR2 is N-myristoylated by Nmyristoyltransferase NMT1 at 22°C, which is important for its interaction with OST1. Moreover, myristoylation of EGR2 is required for its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 59 publications
2
95
0
1
Order By: Relevance
“…Besides clade A PP2Cs, EGR1/2/3 suppress plant growth partially through dephosphorylating microtubule‐associated protein MASP1 at Ser670 and destabilizing microtubules which are required for appropriate levels of growth under osmotic stress (Bhaskara et al 2017). They also inhibit proline accumulation and suppress resistance responses to drought and cold stresses through suppressing SnRK2 activation (Bhaskara et al 2017; Ding et al 2019). Ancient PYL without ABA binding affinity has been reported in algae, while PP2Cs and SnRK2s from algae have conserved functions compared with those from higher plants (Lind et al 2015; de Vries et al 2018; Cheng et al 2019; Sun et al 2019).…”
Section: Core Aba Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides clade A PP2Cs, EGR1/2/3 suppress plant growth partially through dephosphorylating microtubule‐associated protein MASP1 at Ser670 and destabilizing microtubules which are required for appropriate levels of growth under osmotic stress (Bhaskara et al 2017). They also inhibit proline accumulation and suppress resistance responses to drought and cold stresses through suppressing SnRK2 activation (Bhaskara et al 2017; Ding et al 2019). Ancient PYL without ABA binding affinity has been reported in algae, while PP2Cs and SnRK2s from algae have conserved functions compared with those from higher plants (Lind et al 2015; de Vries et al 2018; Cheng et al 2019; Sun et al 2019).…”
Section: Core Aba Signalingmentioning
confidence: 99%
“…The PR5 receptor‐like kinase 2 (PR5K2) may also repress ABA and stress signaling through phosphorylating ABI1/2 and enhancing their protein phosphatase activities (Baek et al 2019). Moreover, function of the clade E PP2C, EGR2 requires myristoylation by NMT1, which is suppressed by cold stress (Ding et al 2019).…”
Section: Core Aba Signalingmentioning
confidence: 99%
“…Cytoplasmic PP2A dephosphorylates the receptor kinase BRI1 to inhibit BR response, but nuclear PP2A dephosphorylates and stabilizes BZR1 to activate BR response (Wang et al, ). Other examples where localization is likely to determine the substrates available to the phosphatase are Clade E PP2Cs that are localized along the plasma membrane and whose putative targets are predominantly membrane and cytoskeleton proteins (Bhaskara, Wen, Nguyen, & Verslues, ; Ding et al, ). Similarly, it was shown that plasma membrane‐associated Clade D PP2Cs affected cell expansion via regulation of plasma membrane AHA phosphorylation, whereas those localized in cytoplasm or other cellular compartments did not (Ren et al, ).…”
Section: Posttranslational Mechanisms Regulating Phosphatase Activitymentioning
confidence: 99%
“…Recently reported functional characterization of the EGR PP2Cs and Clade A PP2C HAI1. Top: EGRs (Clade E PP2Cs) were shown to dephosphorylate and inactivate SnRK2.6 (also known as OST1 or SnRK2E; Ding et al, ). EGRs were also found to regulate the phosphorylation status of microtubule‐associated stress protein 1 (MASP1) as well as additional plasma membrane and cytoskeleton associated proteins (Bhaskara, Wen, et al, ).…”
Section: Pp2cs the Largest Group Of Plant Protein Phosphatasesmentioning
confidence: 99%
“…LTI (LOW TEMPERATURE INDUCED) and RAB (RESPONSIVE TO ABSCISIC ACID) participate in freezing tolerance and osmotic stress [28]. Protein kinase OST1 (OPEN STOMATA 1) enhances freezing tolerance by regulating ICE1 phosphorylation [29,30]. BES1 (BRI1-EMS-SUPPRESSOR 1) played an essential role in BR signal transduction, positively regulating CBF expression [31].…”
Section: Introductionmentioning
confidence: 99%